Surface Treatment for Conductive 12 CaO⋅7 Al2O3 Electride Powder by Rapid Thermal Annealing Processing and Its Application to Ammonia Synthesis. Issue 5 (5th March 2014) - Hayashi, Fumitaka; Kitano, Masaaki; Yokoyama, Toshiharu; Hara, Michikazu; Hosono, Hideo
Abstract The inorganic electride [Ca24Al28O64]4+(e−)4 (C12A7:e−) has unique properties, that is, chemical stability and a low work function comparable to that of metal K. However, its surface area is low (≈1 m2 g−1) because sintering occurs during high‐temperature annealing, which is needed to remove CaO layers formed by reaction with metal Ca that works as a reductant. We report a simple synthesis method for moderate‐surface‐area C12A7:e− (9–19 m2 g−1) by using a rapid thermal annealing (RTA) technique. The synthesis consists of 1) high‐temperature evacuation, 2) reaction with Ca metal, and 3) RTA. The influence of these synthesis conditions was first studied to achieve both high surface area and high electron concentration. Next, C12A7:e− samples were examined as Ru catalyst supports for NH3 synthesis. The activity of Ru‐loaded as‐prepared C12A7:e− was moderate but was increased fivefold by RTA processing prior to Ru loading as a result of surface structure reconstruction. The improvement in the Ru dispersion degree that results from the increased surface area trebled the overall activity (3550 μmol<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5np6rtw8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NH 3</alternatives> gcat−1 h−1 at 340 °C) compared with that of conventional Ru/C12A7:e−.